اشهر الطواعين في التاريخ الاسلامي - حناني فردوس (University of Eloued جامعة الوادي, 2023)
يعد الطاعون من أشد الأوبئة ضراوة عبر التاريخ، فقد عانى المسلمون منه، وكان الحجر الصحي هو الحل الأمثل للتقليل من انتشاره، والحد من ارتفاع نسبة الوفيات، هذه التربية الصحية السليمة التي أرشدنا إليها الرسول  . من أبرز الطواعين التي مست الدولة الإسلامية: طاعون شيرويه (6هـ-127م)، وطاعون عَمَوَاس (18هـ-293م)، الطاعون العظيم بالكوفة (50هـ-670م)، وطاعون الجارف (69هـ-688م)، وطاعون الجارف أو الفتيات والأشراف (87هـ-705م)، وطاعون عدي بن أرطأة (100هـ-718م)، وطاعون غراب (127هـ-744م)، وطاعون مسلم بن قتيبة (131هـ-748م)، وقد ساهمت هذه الأوبئة في سقوط الدولة الأموية. The plague is one of the most virulent epidemics throughout history, Muslims have suffered from it, and quarantine was the best solution to reduce its spread and reduce the high death rate. This is the sound health education that the Messenger of God, peace and blessings be upon him, guided us to. and one of the most prominent plagues that affected the Islamic state: the Shiroeh Plague (6AH-127AD), the Plague of Emmaus (18AH-293AD), the Great Plague in Kufa (50AH-670AD), the Plague of the Great (69AH-688AD), the Plague of the Great or Girls and the Nobles (87AH-705AD), and the plague of Uday bin Arta (100AH-718AD), the plague of Ghorab (127AH-744AD), and the plague of Muslim bin Qutaiba (131AH-748AD), These epidemics contributed to the fall of the Umayyad dynasty
The Most Famous Plagues In Islamic History
Keywords: الوباء؛ الطاعون؛ أشهر الطواعين؛ الحجر الصحي؛ التاريخ.; Epidemic; Plague; The Most Famous Plagues; Quarantine; History.